The Analysis of Translation Method on “Kesombongan Jerapah (The Giraffe Arrogance)” Book: A Children Story - Nur Fajriani, Anisa Ayu; Zumala Dwi Andriani, Zulfi (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2023)
Many people understand English, like in Indonesia. People who understand English give a chance for everyone to understand anything written in English with translation. Thus, translation is very important for knowledge and communication. Translation is integrated into language learning practices along with commonly used learning activities, such as reading, listening, writing, and vocabulary development. Translation is the process of transferring a message or meaning from one language to another language. The object of the study is to explain the method used by the translator in translating the Kesombongan Jerapah (The Giraffe Arrogance) book. This book consists of thirty-two pages and twenty-three sentences. This research is classified into descriptive qualitative research. The descriptive qualitative method is used in this study to uncover the findings using Peter Newmark’s concept of translation method. the data of this research are collected doing the following steps, they were the researcher read Kesombongan Jerapah (The Giraffe Arrogance) children’s storybook in Indonesian version and English version intensively and carefully to comprehend the text thoroughly, the researcher identifies the data, the researcher make tables to analyze data, and the researcher makes a conclusion of the research. The result of the research shows that there are two methods found in the data. They are namely, word-for-word and literal translation methods. The total data are twenty-three sentences of thirty-two pages. There are seventeen sentences using word-for-word translation methods and six sentences using literal translation methods.